The Effect of Watery & Alcoholic Plant Extracts of Elettaria cardamomum On Growth of Some Bacteria Isolated from Otitis media Infections - Mahmood, Z.S.N.; Khalil, M.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study was done to determine the effect of watery and alcoholic extracts of Elettaria cardamomum on growth of bacteria isolated from Otitis media Infections which are : Pseudomonas aeruginosa , Staphylococcus aureus and Klebsilla spp. The biochemical analysis revealed that watery extracts of Elettaria cardamomum contains: Glycosides, Alkaloids, Saponines, Tannins, and Volatile oils, ( This compound is Soluble in water ) , while the alcoholic extracts contains : (in addition to the above mentioned compounds ) Phenols , Resins , Flavonids and Coumarins. ( This compound is Soluble in organic solutions ). To study the effect of watery and alcoholic extracts of Elettaria cardamomum on growth of bacteria isolated from Otitis media Infections, we make four extracts ( cold watery extract , hot watery extract , cold alcoholic extract and hot alcoholic extract. The study shows that (hot alcoholic extract ) was more effective than the other extracts, by using agar diffusion method (wells). The study also showed that staphylococcus aureus ( gram positive ) bacteria is more sensitive to plant extracts than the gram negative bacteria , while Pseudomonas aeruginosa was more resistant to plant extracts than the others.